Boys will be “Boys”: Variability in Boys’ Experiences of Literacy - Sokal, Laura; Katz, Herb; Adkins, Matthew; Gladu, Andrea; Jackson-Davis, Khalie; Kussin, Brian (Alberta Journal of Educational Research, 2005)
Sixty-nine grade 2 boys participated in a study of the effects of book genre and sex of reading model on boys’ (a) view of reading as feminine, (b) intrinsic motivation toward reading, (c) interest in reading, and (d) attitude to reading. Differential effects occurred in boys based on whether they liked or disliked reading and whether they viewed reading as a feminine activity. Findings are examined in the context of gender schema theory as a way of explaining why boy-friendly books are important to some boys’ reading development and not to that of others.